2022
DOI: 10.3389/fpubh.2022.824073
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of External Debt on Health in an Emerging Asian Economy: Does FDI Matter?

Abstract: In this study, our main objective is to find the impact of FDI and external debt on health outcomes in emerging Asian economies from 1991 to 2019. To that end, we have collected data for seven economies: Bangladesh, Malaysia, Philippines, Thailand, Sri Lanka, China, and India. We have relied on the panel ARDL (PARDL) method for empirical analysis. The study's findings confirmed that the debt has increased infant mortality and decreased life expectancy in emerging Asian economies in the long run. On the other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Empirically, the study showed that unsustainable, illiquid, and insolvent external debt and macroeconomic volatility shorten longevity in West African countries. Hence, longevity will decline when weak external debt management promotes poverty not just in West Africa but also in other developing countries, as reported in empirical studies (such as Loko et al, 2003); Saungweme and Mufandaedga, 2013;Zaghdoudi and Hakim, 2017;and Ma et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Empirically, the study showed that unsustainable, illiquid, and insolvent external debt and macroeconomic volatility shorten longevity in West African countries. Hence, longevity will decline when weak external debt management promotes poverty not just in West Africa but also in other developing countries, as reported in empirical studies (such as Loko et al, 2003); Saungweme and Mufandaedga, 2013;Zaghdoudi and Hakim, 2017;and Ma et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, Ma et al (2022) tried to establish the effect of external indebtedness on health outcomes in the emerging economies of Sri Lanka, Bangladesh, India, Thailand, Malaysia, China and the Philippines. The study employed the panel ARDL methodology and concluded that external debt aggravates infant mortality and diminishes life expectancy in the examined countries in the long term.…”
Section: Effect Of External Debt On Life Expectancymentioning
confidence: 99%
“…The study observed that public and household debt contribute substantially to the standard of living in the country. Likewise, Ma et al ( 2022 ) tried to establish the effect of external indebtedness on health outcomes in the emerging economies of Sri Lanka, Bangladesh, India, Thailand, Malaysia, China and the Philippines. The study employed the panel ARDL methodology and concluded that external debt aggravates infant mortality and diminishes life expectancy in the examined countries in the long term.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results can vary greatly depending on how health is measured [ 57 ]. Most previous studies used two common proxies: premature mortality and life expectancy rates at birth [ 6 , 37 , 58 ]. However, these sample-level data cannot accurately measure the health level of the individual.…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…Furthermore, the causal pathway detected in existing studies varies [ 37 ]. The causation between debt and individual health is likely to run in both directions [ 35 ]: some measures of microcredit are found to affect health, whereas other measures of health are found to affect microcredit [ 27 ].…”
Section: Introductionmentioning
confidence: 99%